2022
DOI: 10.3390/ijerph19137626
|View full text |Cite
|
Sign up to set email alerts
|

Greater Emotional Distress Due to Social Distancing and Greater Symptom Severity during the COVID-19 Pandemic in Individuals with Bipolar Disorder: A Multicenter Study in Austria, Germany, and Denmark

Abstract: Throughout the COVID-19 pandemic, mental health of individuals with bipolar disorders (BD) is potentially more vulnerable, especially regarding COVID-19-related regulations and associated symptomatic changes. A multicentric online study was conducted in Austria, Germany, and Denmark during the COVID-19 pandemic. Overall, data from 494 participants were collected (203 individuals with BD, 291 healthy controls (HC)). Participants filled out questionnaires surveying emotional distress due to social distancing, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
(60 reference statements)
0
5
1
Order By: Relevance
“…The COVID‐19 pandemic has impacted patients with various psychiatric disorders, including increasing the prevalence of depressive symptoms 1 . In particular, patients with bipolar disorder (BD) have been reported to experience stronger psychological distress than healthy controls or patients with other psychiatric disorders 2–4 . In patients with BD, the lockdown was found to worsen manic and other symptoms 4,5 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The COVID‐19 pandemic has impacted patients with various psychiatric disorders, including increasing the prevalence of depressive symptoms 1 . In particular, patients with bipolar disorder (BD) have been reported to experience stronger psychological distress than healthy controls or patients with other psychiatric disorders 2–4 . In patients with BD, the lockdown was found to worsen manic and other symptoms 4,5 .…”
Section: Figurementioning
confidence: 99%
“… 1 In particular, patients with bipolar disorder (BD) have been reported to experience stronger psychological distress than healthy controls or patients with other psychiatric disorders. 2 , 3 , 4 In patients with BD, the lockdown was found to worsen manic and other symptoms. 4 , 5 However, curfew restrictions in Japan have not been as strict as those in Western countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Schönthaler et al (2022) showed COVID-19 fears to be elevated in clinical and non-clinical samples in times of higher infection and mortality during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we investigated the bidirectional connection between resilience, COVID-19 work-related fears, and anhedonia within WHS. While previous studies focused on the impact of resilience within psychiatric patients (Dalkner et al 2021;Fleischmann et al 2022;Schönthaler et al 2022;Min et al 2013), patients with chronic diseases (Buscetta et al 2022;Kim et al 2019;Sbragia et al 2022;Tso et al 2020), and cancer Seiler and Jenewein (2019), as well as child development, Masten and Reed (2002), the application of resilience concepts to the workplace is relatively new. Without the burden of a pandemic situation, King et al (2016) had already discussed the necessity of including resilience, a thus far overlooked concept into today's organizations.…”
Section: Introductionmentioning
confidence: 99%